Implicit Feedback for Inferring User Preference: A Bibliography - Kelly, Diane; Teevan, Jaime (SIGIR Forum, 2003)
Relevance feedback has a history in information retrieval that dates back well over thirty years. Relevance feedback is typically used for query expansion during short-term modeling of a user's immediate information need and for user profiling during long-term modeling of a user's persistent interested and preferences. In this paper we consider the use of implicit feedback techniques for query expansion and user profiling in information retrieval tasks.